Alpha particle autoradiography for high spatial resolution mapping of radionuclides. (February 2019) - Kalnins, Christopher A.G.; Spooner, Nigel A.; Clarke, Michael J.P.; Ottaway, David
Abstract: An autoradiographic technique capable of determining the spatial location of radioactive isotopes within materials on the scale of micrometers is demonstrated in low-activity mineral samples, where the concentrations of radionuclides with short half lives is small and below the detection limits of current measurement techniques. The location of certain radionuclide species within samples with complex structures on the micron scale can yield valuable information, however current methods do not have the spatial resolution required for this purpose. We demonstrate the use of an autoradiographic emulsion to directly image alpha particle events in samples with low radionuclide concentrations, allowing spatial resolution of radionuclide locations on the order of several microns. Exposure over a long time period allows sufficient integration of decay events enabling analysis of samples with low activity but large area, (less than 1 × 10 − 4 Bq/mm 2 ). The use of polarising filters to increase contrast between the alpha particle tracks and the substrate during imaging demonstrates the viability of the technique on samples with a complex structure.